2013
DOI: 10.1371/journal.pone.0080871
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Affect Proliferation of Salmonella in Tomatoes Post-Harvest: The Roles of Seasonal Effects, Irrigation Regime, Crop and Pathogen Genotype

Abstract: Main ObjectivesFresh fruits and vegetables become increasingly recognized as vehicles of human salmonellosis. Physiological, ecological, and environmental factors are all thought to contribute to the ability of Salmonella to colonize fruits and vegetables pre- and post-harvest. The goal of this study was to test how irrigation levels, fruit water congestion, crop and pathogen genotypes affect the ability of Salmonella to multiply in tomatoes post-harvest.Experimental DesignFruits from three tomato varieties, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 45 publications
3
31
0
Order By: Relevance
“…can proliferate within red ripe tomato pericarps, reaching ϳ10 7 CFU per fruit (9,19,21,25,35). To represent the entire transposon insertion library, the screening needed to be done using an inoculum titer very close to the carrying capacity of tomatoes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…can proliferate within red ripe tomato pericarps, reaching ϳ10 7 CFU per fruit (9,19,21,25,35). To represent the entire transposon insertion library, the screening needed to be done using an inoculum titer very close to the carrying capacity of tomatoes.…”
Section: Resultsmentioning
confidence: 99%
“…Biosynthesis of amino acids was also a likely factor required for Salmonella growth in alfalfa root exudates (15). Plant colonization by Salmonella is affected by host factors; the genetic background can influence Salmonella colonization of sprouts (18), proliferation in the tomato phyllosphere (19,20), and pericarps (21).…”
mentioning
confidence: 99%
“…Very few research studies have evaluated the impact of seasonality on the proliferation of Salmonella in fresh produce. Marvasi et al (2013) found that the driest and sunniest seasons were the most conducive to post harvest proliferation of Salmonella and tomatoes. However, this study only identified an indirect effect of the climatic conditions as the seasonal effects were only evaluated on the post-harvest proliferation of Salmonella.…”
Section: Climatic Conditionsmentioning
confidence: 99%
“…In addition to the quality of the irrigation water, irrigation practices in terms of amount of water may also affect the susceptibility of tomatoes to post-harvest Salmonella growth inside tomatoes. Marvasi et al (2013) reported that artificial soaking of tomato pericarp tissues in water caused a 10-fold increase of inoculated Salmonella growth. However, these authors could not reproduce such an increase of Salmonella growth by over irrigating field grown tomatoes.…”
Section: Water Use During Production (Irrigation Pesticides and Fertmentioning
confidence: 99%
“…Aristotle) and tomatoes Bonny Best and Solar Fire). All data for tomatoes of the three varieties were combined to serve as a broader basis for comparison, while a more comprehensive analysis of the responses of different tomato varieties to different irrigation regimes is reported elsewhere (Marvasi et al, 2013). As shown in Fig.…”
Section: Responses Of Pepper and Tomatoes To Different Irrigation Regmentioning
confidence: 99%